DEVELOPMENT OF MODERN BUSINESS PROCESSES AND OUTSOURCING ACTIVITIES - Khalatur, Svitlana; Vinichenko, Igor; Volovyk, Dmytro (Baltic Journal of Economic Studies, 2021)
The purpose of the article is to study the key features of modern business processes and outsourcing. The subject-matter of the study is the methodological and conceptual foundations of the development process of modern business and outsourcing activities. Methodology. The research is based on a set of well-known general scientific and special methods of research in economics. In particular, the method of scientific abstraction, the method of systematic analysis, economic and mathematical modeling were used in the article. Conclusion. Many types of modern work can be outsourced. Thus, this will eventually lead to a confrontation between protected freelancers and freelancers whose employment is not regulated at the legislative level. The world is changing much faster, the labor market is undeniably affected when most jobs are simplified by technology; one of the consequences is a departure from the usual regulated labor relations and structures. The work environment and the environment are changing radically today. New forms of cooperation can take legal relations beyond legal regulation in those countries that fail to adapt their legislation in time to new rapidly evolving business strategies, which often lack the concept of territorial boundaries and mostly demand talent for effective solutions. With the help of constructed multifactor regression models, which are adequate to the available statistical and calculated data and have high degrees of significance of the estimated parameters, it is possible to predict changes in the simulated economic phenomenon as a result of changes in one or more factors. It should be noted that such models today are not sustainable in the long run, as in the Ukrainian and global economies, the external environment and its conditions change quite often. Therefore, in the future it is advisable to calculate new parameters of regression models based on the presented methods and make predictions according to the obtained data. In authors’ opinion, the main reason for the increase in the share of outsourcing in Europe in the coming years is the strengthening of competition in the world market and the growth of the euro. It is believed that traditionally vertically integrated business processes will be broken into fragments and partially outsourced. This will allow European companies to increase their revenues and production volumes.